PENGARUH LATIHAN FISIK JALAN KAKI TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE II DI KOTA PADANG - Sp.Kom, Tasman.S.Kp.M.Kep. (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Recently Tipe II Diabetes Mellitus has been one of associated with Physical Exercise is less.One of sport are recommended in patient with Type 2 Diabetes Mellitus is walking. Howeverthe study about the effect of physical activity: walking to decrease blood glucose levels. Thepurpose of this study was to determine the influence of physical activity: walking to decreaseblood glucose levels in patients with Type II Diabetes Mellitus. The research was conducted inthe Working Area of Public Health Pauh Padang and the implementation of interventions ineach respondent’s stayed. When the study began from February to July 2013. The design of thestudy is a pre-experimental design with One group pretest-posttest Design approach. Thesampling technique was purposive sampling with a sample of 21 respondents. Data wascollected by measurement of blood glucose levels directly. The data analysis was performedwith the Paired Sampel T-Test to assess the differences before and after intervention. Theresults of this study show an average reduction in blood glucose levels with walking exercise is50 mg/dl. The result of statistical test obtained the value p = 0.000 (p <0.05) which means itcan lower blood glucose levels in patients Type II Diabetes Mellitus. Advised to make a groupsof walking exercise for patients Type II Diabetes Mellitus to controls their blood glucoselevels.Keywords: Type II Diabetes Mellitus, walking